How technological innovation and organizational culture influence circular economy adoption over time in Saudi Arabian manufacturing - Naima Sadaoui; Houcine Benlaria; Naeimah Fahad Almawishir; Balsam Saeed Abdelrhman; Sumaya Awad Khader Ahmed; Lotfi Zabat; Badreldin Mohamed Ahmed Abdulrahman; Rania Alaa Eldin Ahmed Khedr (Discover Sustainability)
Abstract This study explores the factors influencing circular economy adoption, a critical endeavor to achieve sustainability and environmental goals. Our study focuses on 222 people in executive and sustainability officer positions in different parts of the Kingdom of Saudi Arabia (KSA), who are actively involved in adopting new technologies and promoting the circular economy. We used Structural Equation Modeling (SEM) to examine how new technologies, organizational culture, supply chain integration, employee attitudes, and time affect the adoption of the circular economy. The results show that new technologies have a significant effect on the adoption of a circular economy (β = 0.177, p < 0.01) and the model can explain 70.9% of the variation in adoption. Supply chain integration (β = − 0.103, p < 0.05) and employee attitudes (β = 0.195, p < 0.001) demonstrated significant mediating effects, whereas organizational culture showed a non-significant mediating role. Our study highlights the critical moderating role of time on technological innovation (β = 0.281, p < 0.01), supply chain integration (β = − 0.297, p < 0.01), and employee attitudes (β = 0.177, p < 0.05), suggesting the evolution of these factors. To put these ideas into action, our research stresses the importance of putting money into R&D for sustainable technologies, creating organizational cultures that value sustainability, encouraging collaboration in the supply chain, and supporting positive employee attitudes through broad development programs. These findings provide valuable guidance for advancing circular economy adoption in Saudi Arabia’s manufacturing sector.